HUBUNGAN GAJI DENGAN KEPUASAN KERJA PADA PEGAWAI NEGERI SIPIL - Abdullah Sabiq; Feryana Dwi Rahayu (Ilmu Psikologi Universitas Yudharta Pasuruan)
Abstrak Doing a job with a maximum, we need to have a job satisfaction in order to carry out our responsibilities to the maximum. According to many people, is the strongest factor supporting work satisfaction on an employee. Given the soaring cost of living, the price of goods is increasingly expensive, not yet academic fees, medical expenses, and others are increasing. This research was conducted to determine the relationship between salary and job satisfaction in civil servant. The research instrument used was a job satisfaction scale and a salary questionnaire. The sampling technique in this study used a non random sampling technique with a quota sampling type. The sample used was the Surabaya City Health Department civil servants, as many as 50 people. The data obtained were analyzed using one predictor regression analysis technique. From the proper results obtained rxy of 0.254. So rxy < rtab 5% = 0.279. Thus there is no significant correlation between salary and job satisfaction.